Two‐Dimensional Red Phosphorus Nanosheets: Morphology Tuning and Electrochemical Sensing of Aromatic Amines. Issue 10 (9th September 2021) - Liu, Lingbo; Shen, Jian; Wu, Kangbing; Yang, Nianjun
Abstract: Synthesis of 2D materials with different morphologies is of significance to reveal their morphology‐dependent properties and further explore their morphology‐dependent applications. This work reports the synthesis of 2D red phosphorus nanosheets (RPNSs) with different thicknesses by means of a phosphorus‐amine method together with regulated electrophilicity of the solution. With graphene as the support, the RPNSs produced in 0.01 m HCl feature a unique 2D nanostructure, uniform distribution, and excellent electrochemical performance. Originating from the reacted characteristics between phosphorus and amine, the interaction of aniline with the RPNSs is clarified theoretically and experimentally by means of density functional theory, X‐ray photoelectron spectroscopy, and voltammetry. A covalent bond is confirmed to be formed during the deprotonation of aniline and its binding energy reaches −2.31 eV. Stemming from such an adsorption process, different aromatic amines (e.g., p‐nitroaniline, p‐phenylenediamine) are sensitively and selectively monitored on the RPNSs. Consequently, this work provides a new way to clarify morphology‐dependent properties and applications of novel 2D materials. Abstract : Red phosphorus nanosheets with different thicknesses are deposited on graphene through a phosphorus‐amine method and regulated electrophilicity of the solutions. Those produced in 0.01 m HCl feature a unique 2D nanostructure and excellent electrochemical performance. The NP bond is formed on the nanosheets during the deprotonation of amine, leading to the establishment of highly sensitive electrochemical sensors toward different amine compounds.